2009
DOI: 10.1002/jemt.20741
|View full text |Cite
|
Sign up to set email alerts
|

Effects of di(2‐ethylhexyl) phthalate on gap and tight junction protein expression in the testis of prepubertal rats

Abstract: The aim of this study was to analyze whether di(2-ethylhexyl) phthalate (DEHP), a Sertoli and Leydig cell toxicant, is able to induce alterations in the expression of testicular gap and tight junction proteins. DEHP was administered by gavage (1 g/5 mL corn oil/kg body weight/day) to 25-day-old male Sprague-Dawley rats for 2 days (DEHP-27d) and control rats were treated with corn-oil vehicle for 2 days (C-27d); animals were killed 24 h after the last treatment. Testes of DEHP-27d rats showed different degrees … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 42 publications
1
29
0
Order By: Relevance
“…DEHP and MEHP induce germ cell sloughing that might be associated with downregulation of claudin-11, occludin, Cx43, and ZO-1 and changes in cell junction proteins of BTB [33]. In addition, exposure to MEHP decreases the inhibition of metalloproteinase-2 expression in testes tissue, which allows for matrix metalloproteinase 2 activation, leading to the remodeling of tight junctions between adjacent Sertoli cells [34]. On the other hand, many reports have also shown that while DEHP itself is not an immunogenic antigen, it can act as an adjuvant [4][5][6][7][8].…”
Section: Discussionmentioning
confidence: 97%
“…DEHP and MEHP induce germ cell sloughing that might be associated with downregulation of claudin-11, occludin, Cx43, and ZO-1 and changes in cell junction proteins of BTB [33]. In addition, exposure to MEHP decreases the inhibition of metalloproteinase-2 expression in testes tissue, which allows for matrix metalloproteinase 2 activation, leading to the remodeling of tight junctions between adjacent Sertoli cells [34]. On the other hand, many reports have also shown that while DEHP itself is not an immunogenic antigen, it can act as an adjuvant [4][5][6][7][8].…”
Section: Discussionmentioning
confidence: 97%
“…In the latter study, a surge in the protein level of CLAUDIN11 was observed but its levels at the cell surface remained unchanged. In another study, the effects of the reproductive toxicant di(2-ethylhexyl) phthalate (DEHP) on testicular gap and tight junction protein expression were investigated in prepubertal rats (Sobarzo et al 2009). There it was shown that DEHP did not impair BTB permeability but induced GC sloughing that was accompanied by a downregulation of CX43 and ZO1 and alterations in other junctional proteins (Sobarzo et al 2009).…”
Section: Cx43 and Scmentioning
confidence: 99%
“…Similarly, postnatal toxicant exposure, through lactation, and prepubertal treatment of animals resulted in a reduction of testicular Cx43 expression, associated with germ cell sloughing and infertility. 117,140,142 Other authors reported that exposure of immature rats via lactation to a mixture of xenoestrogens (17-α-ethinyl estradiol, bisphenol A and alkyl phenols) exerted long-lasting deleterious effects on epididymal sperm concentration and motility and at the same time reduced Cx43 expression in the seminiferous epithelium, suggesting that the intercellular coordination of testicular function may be affected. 124 In addition to disrupt Cx43 gap junction functionality, recent studies demonstrated that a blockade of the channel coupling by BPA gives rise to signs of germ cell loss, resulting from Sertoli cell bloodtestis barrier impairment (BTB).…”
Section: Connexin Expression Function and Regulation In The Developimentioning
confidence: 99%